A case study on environmental factors affecting user traffic at the College of Arts and Letters library - Mararac, Caren Cyel G.; Dorado, Dan Anthony D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
Many factors need to be present in a specific library environment to achieve maximum efficiency in meeting its users' needs. Several other factors influence the users' intention to enter and stay in the library. This study focused on the environmental factors affecting user traffic at the College of Arts and Letters Library.
This study sought to determine (1) the environmental characteristics of the CAL Library which affect the learning of its users; (2) how these environmental characteristics affect library usage; and (3) identify means to make the CAL Library more conducive to users.
Fifty-eight respondents who have visited and stayed at the College of Arts and Letters Library were surveyed. The respondents were asked to answer a survey questionnaire containing the following needed information: (1) profile of the respondents; (2) library usage; (3) users' perception towards the environmental factors of the library; (4) users' assessment of the CAL library; (5) comments and suggestions to consider for improvement.
An interview with the licensed librarians of the College of Arts and Letters was also conducted to obtain credible information and insights which are deemed crucial in this study. Moreover, a focus-group discussion was facilitated to acquire a free-flowing exchange of beliefs, perceptions, views, and opinions, on the matter at hand.
Despite the physical/environmental difficulties identified by the librarians, most respondents agreed that space allocation, presence of ample furniture and equipment, arrangement of tables and chairs, presence of cooling devices, and thermal comfort are the most common factors that affect user traffic. Likewise, factors such as noise level and approachability of library personnel-both of which could be considered psychosocial factors rather than purely physical/environmental-were considered by more than half of the respondents influential. However, at the end of the study, accomplishment of activities or tasks still ranked highest among the reasons for using the library.
Despite the library lacking in some areas as rated by the respondents, overall satisfaction regarding its use remains high. However, improvements through renovation, rearranging, and redesigning are recommended by the librarians as well as the results of the focus discussion group.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) College of Arts and Letters Library -- Use studies; Library use studies -- Philippines -- Quezon City